Atoms for electricity generation in Africa: Analysis of factors affecting the continent’s readiness; Progress in Nuclear Energy; Vol. 141 - Ansakh M. N. S. Maykl Nii Sanka; Ageykum E. B. Efraim Bona; Amoah P. A. Paul Atta; Afornu B. K. Bright Kwame (2021, 2021)
Title screen